2020
DOI: 10.3934/ipi.2020014
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous reconstruction of emission and attenuation in passive gamma emission tomography of spent nuclear fuel

Abstract: The International Atomic Energy Agency (IAEA) has recently approved passive gamma emission tomography (PGET) as a method for inspecting spent nuclear fuel assemblies (SFAs), an important aspect of international nuclear safeguards which aim at preventing the proliferation of nuclear weapons. The PGET instrument is essentially a single photon emission computed tomography (SPECT) system that allows the reconstruction of axial cross-sections of the emission map of the SFA. The fuel material heavily self-attenuates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…A quantitative evaluation of the activity distribution using these devices would require detailed, and sometimes difficult-to-asses, knowledge of the spatial attenuation distribution of the full measurement geometry as well as a characterised detector system where intrinsic detection efficiencies need to be well understood. Backholm et al (2020) have tested simultaneous reconstruction of the spatial distributions of both attenuation and activity, however still producing images with relative data used for classification of the presence or absence of a nuclear fuel rod.…”
Section: Overview and Backgroundmentioning
confidence: 99%
“…A quantitative evaluation of the activity distribution using these devices would require detailed, and sometimes difficult-to-asses, knowledge of the spatial attenuation distribution of the full measurement geometry as well as a characterised detector system where intrinsic detection efficiencies need to be well understood. Backholm et al (2020) have tested simultaneous reconstruction of the spatial distributions of both attenuation and activity, however still producing images with relative data used for classification of the presence or absence of a nuclear fuel rod.…”
Section: Overview and Backgroundmentioning
confidence: 99%
“…While the former can be mitigated using collimated detectors, the latter needs to be addressed by using specific imaging algorithms. Previous work has shown that the reconstruction quality could be significantly improved by applying the attenuation correction 8 . In this work, we further corrected for the gamma ray down-scattering in the energy window of interest.…”
Section: Introductionmentioning
confidence: 99%
“…For any safeguards investigation of SFAs, it is important to use a minimum amount of a priori information on the SFA under study, in order to avoid biasing and potentially misleading the investigation. Eventually, IAEA approved the use of the passive gamma emission tomography (PGET) instrument [2][3][4][5][6][7] in inspections.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in [7], the authors proposed a method to simultaneously reconstruct the activity and attenuation maps by formulating the reconstruction as a constrained minimization problem with a least squares data fidelity term and quadratic regularization terms with different smoothness matrices. However, the forward model proposed in [7] considered only monoenergetic gamma rays and did not account for the scattering effects of gamma rays in the PGET system that make non-neglible contributions to the total counts, which added additional uncertainty to the activity estimation results. Similarly, in [22], the authors formulated the problem of pin activity estimation as an optimization problem where a sparse regularization function is used.…”
Section: Introductionmentioning
confidence: 99%